(3GdTGed aj GdUfGYI GdWHjIs - (3GHf GdfajS , YdGA GdOjf CHh GdMSf Ydj Hf CHj GdMRe GdbQTj, GHf GdfajS,J (B687 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje heG Jhajbi EdG HGddg Ydjg JhcdJ GdcJGH GdSGHY ef GdLRA GdKGfi ef Gdaf GdKGdK ef cJGH GdTGed ai GUfGYI GdWHjI , hbUOfG ajg Cf fJcde ai GdCOhjI hGdCZPjI GdeaQOJjf GddJjf Chd CSeGFgeG MQa GdNGA s
(3BNQgG (B:s
(3MH GdQeGf GdMGeV Ch eY GdJeQ GdgfOi aEf Pdc HbhI MehVjJg jefY ESJMGdI gPG GdeTeT Edi GdeQGQ hjfHZi Cf jchf JfGhdg eY TF ef GdScQ hfMhg hPdc dCfg EPG de s
(3GdeLdO GdQGHY hGdCQHYhf JbQjHkGs
(3GSJfGOkG Edi GdhUa GdPi bOeg GdOcJhQ fbhdGgjQ ddeLdO GdKGdK hGdCQHYjf ef fSNI LGeYI SJGfahQO ai cGdjahQfjGs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B270 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B58s
Keywords: (3GdWHs